Impact of Pilot Fatigue and Sleep Deprivation on Cognitive Performance and Flight Safety – A Narrative Review - Latalska, Katarzyna; Leja, Wiktoria; Błaszczak, Maciej; Zulfiqar, Zeeshan; Kot, Jakub; Czechowicz, Katarzyna; Szczupaj, Maciej; Pastuszak, Andżelika; Borkowski, Konrad; Rudnicki, Jakub (Quality in Sport, 2026)
Pilot fatigue and sleep deprivation are two very serious and persistent risks to global aviation safety. In particular night flying and cross-continental travels result in a continuous fatigue build-up and may lead to diminished pilots’ performance. This review combines findings from recent research concerning the impact of sleep loss and fatigue on the cognition of pilots. In particular factors like working memory, focusing attention, reaction times, decision making and situational awareness are discussed. The presented review demonstrated that moderate levels of sleep deprivation lead to measurable decreases in human alertness, psychomotor speed and executive functioning. Moreover, it was proved fatigue played a pivot role in a large number of aviation incidents and accidents. Presented reports indicate that aviation regulatory agencies, airline managers and researchers should give high priority to reducing pilot fatigue in order to protect both the health of pilots and the safety of passengers.